Prediction of the viscosity of a water - base mud treated with cassava starch and potash at varying temperatures using factorial design (2007)
In order to monitor and control the properties of drilling fluids, measurements are routinely made at the surface. However, these surface measurements may not be representative of down-hole properties where the desired functions of hole cleaning and other related issues are critical to the success of the drilling operations. Consequently, it is important to make necessary adjustments of the fluid properties obtained at ambient conditions to give estimate of properties at high temperatures and pressures. The principle and method of factorial design have been used to develop a model, which makes possible the prediction of drilling fluid viscosity at varying temperatures. Cassava starch and potassium carbonate were used as local additives in a water based bentonic drilling fluid after running a quality check 23 full factorial design experiments which consider temperature, starch and potash as factor variables and viscosity as the response variable were conducted. The main effects as well as the interaction effects were determined and examined. The results were analyzed and a predictive model was obtained. Viscosity values obtained using the model were compared with the experimental results and it was observed that the model has an accuracy of93.6%. This method makes possible the prediction of the viscosity of drilling fluids at varying temperatures, hence the treatment of mud systems can be determined ahead of time.